The Efficiency of Air-Drying Pared Corms of Banana Suckers in Reducing the Risk of Soil-Mediated Xanthomonas Wilt Infections in Ethiopia - Shehabu, Meki; Addis, Temesgen; Turyagyenda, Laban Frank; Alemu, Tamiru; Mekonen, Shiferaw; Blomme, Guy (Tree and Forestry Science and Biotechnology, 2010)
Xanthomonas wilt caused by Xanthomonas campestris pv. musacearum is one of the most threatening constraints to banana and enset (Ensete ventricosum) production in Ethiopia. The disease was unknown outside of Ethiopia until it was reported in Uganda in 2001. Since then the disease has spread to many East and Central African countries. Xanthomonas campestris pv. musacearum can only enter a plant through mechanical wounds (e.g. inflicted by garden tools) or natural wounds (e.g. male flower scars). Corm paring is a good practice for the control of weevils and nematode pests in banana but when the practice is conducted and corms planted in Xanthomonas wilt infected fields, Xcm infection occurs. As a solution, curing of corms before planting has been recommended. It is however not known if the recommendation could be adopted in Ethiopia. The study was therefore initiated to evaluate the efficiency of air-drying pared corms of banana suckers in reducing the risk of soil-mediated Xanthomonas Wilt infections under conditions prevailing in Ethiopia. Four treatments, i.e., pared and immediately planted, non-pared and immediately planted, pared and air-dried for three days and non-pared and air-dried for three days were tested for ‘Pisang Awak’ and a ‘Matooke’ genotype in a pot experiment. A total of 30 plants were used for each of the treatments per genotype. The disease incidence was recorded during six months after planting. Samples from dead or wilted plants were collected and plated on a YPSA medium at 28°C to confirm whether the disease symptoms were due to Xanthomonas campestris pv. musacearum. Paring and air-drying of banana suckers before planting increased soil-mediated Xanthomonas wilt infections. To reduce soil-mediated Xanthomonas infections, suckers should be carefully uprooted to avoid wounding and the uprooted suckers should be planted immediately after uprooting.
Keywords: Xcm infection; planting material